Implementasi Peraturan Daerah Kabupaten Bangli Nomor 2 Tahun 2018 tentang Rencana Induk Pembangunan Kepariwisataan Daerah Tahun 2019-2025 terhadap Pengembangan Desa Wisata Dimasa Pandemi Covid-19 - I Komang Tresnanda Pramana; I Nyoman Putu Budiartha; I Gusti Agung Ayu Gita Pritayanti Dinar (Jurnal Interpretasi Hukum, 2022)
The implementation of Bangli Regency Regulation Number 2 of 2018 concerning the Master Plan for Regional Tourism Development for 2019-2025 has not been optimal, due to the covid-19 pandemic. Thus, this study aims to determine and describe the implementation of the District Regulation Bangli No. 2/2018 on the development of tourist villages during the covid-19 pandemic; and to find out the obstacles and efforts of the Bangli district government in implementing the District Regulation. Bangli No. 2/2018 on the development of tourist villages during the covid-19 pandemic. This study uses empirical research methods, namely by collecting data through observation and interviews to the research location. Data were analyzed descriptively. The results of this study found that the Covid-19 pandemic had an impact on the implementation of the District Regulation. Bangli No. 2/2018, in which the implementation of this regulation has not been fully implemented as previously intended. This is because there are obstacles in the implementation of the Regional Regulation itself.